2021
DOI: 10.1029/2021jd035387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atmospheric Attenuation on the Lightning Spectrum

Abstract: Spectrum carries important information reflecting atomic and molecular processes inside a light source. Accurate spectral diagnosis is vital in revealing the microscopic physical mechanism of the lightning discharge process. Spectral correction was applied considering the influence of atmospheric attenuation, grating efficiency, and camera response on the observed spectrum, thereby solving the problems of atmospheric attenuation in long‐distance lightning spectrum observations. Based on the restored spectrum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Due to the randomness of natural CG lightning occurrences and observation conditions as well as discharge environmental restrictions, NI (3) and NI (2) cannot be distinguished well in previously observed spectra of natural CG lightning (An et al, 2021;Liu et al, 2019;Wan et al, 2021;Wang, Yuan et al, 2016. By focusing on lightning discharge processes on tall structures, we obtained spectral data with better wavelength resolution.…”
Section: Optical Thicknessmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to the randomness of natural CG lightning occurrences and observation conditions as well as discharge environmental restrictions, NI (3) and NI (2) cannot be distinguished well in previously observed spectra of natural CG lightning (An et al, 2021;Liu et al, 2019;Wan et al, 2021;Wang, Yuan et al, 2016. By focusing on lightning discharge processes on tall structures, we obtained spectral data with better wavelength resolution.…”
Section: Optical Thicknessmentioning
confidence: 97%
“…It was concluded that the lightning stroke should be optically thin to neutral nitrogen (NI) and neutral oxygen (OI) radiation in the near‐infrared spectrum. In subsequent studies, researchers all assumed that the lightning channel was optically thin to the NI and OI lines in the near‐infrared band when they analyzed the lightning spectrum quantitatively (Boggs et al., 2021; Walker & Christian, 2017; Wan et al., 2021). Due to the lack of spectral resolution in past experimental systems (Uman, 1969), there has been no direct experimental verification of the optical thickness of lightning NI and OI radiation in the near‐infrared spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [34] analyzed a single sprite produced using a mesoscale convective system (MCS). In addition, the spectra of the lightning were observed [35,36], and its physical parameters, such as the electron temperature, density, and conductivity in the channel, were quantitatively calculated, thus allowing the microphysical information inside and around the channel to be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Walker与Christian [4] 基于一次人工触发闪电五个回击的光谱资料和通 道底部电流分析了通道的温度、粒子数密度、亮 度和内部压力等物理参数. 欧阳玉花等 [5] 选用多 条NII谱线, 基于玻尔兹曼图法(Boltzmann plot method)估算了闪电回击通道的温度, 并与二谱线 法做了比较. 他们发现玻尔兹曼图法可以消除二谱 线法因选用不同的谱线组合所引起的不确定因素.…”
unclassified